Use of Nicergoline as Adjunctive Treatment of Neurotrophic Keratitis in Routine Clinical Practice: A Case Series. (17th November 2022) - Miguel-Escuder, L.; Rocha-de-Lossada, C.; Sabater-Cruz, N.; Sánchez-González, José-María; Spencer, F.; Marín-Martínez, S.; Batlle-Ferrando, S.; Carreras Castañer, X.; Torras, J.; Peraza-Nieves, J.
ABSTRACT: Purpose: To describe the effectiveness and safety of nicergoline in patients with epithelial corneal defect or corneal ulcer due to neurotrophic keratitis (NK). Methods: A prospective case series review was performed in 14 patients with NK who started treatment with nicergoline as an off-label prescription from January to November 2020. Patients with a epithelial defect or corneal ulcer due to NK were treated with oral nicergoline. Results/Serial cases: Complete corneal healing was observed in 10 (71.4%) of the 14 patients after 25.6 ± 26.60 days (range 7–90) with nicergoline. In three (21.5%) patients wound healing was not achieved, and one patient (7.1%) was lost to follow-up. The mean time between diagnosis and the starting of nicergoline was 10.92 ± 8.85 days (0–28). No adverse effects of nicergoline were observed. Conclusion: Nicergoline as an adjunctive treatment for NK showed a potential use in the healing of epithelial defect in real-life clinical practice.